Apologetic preaching proclaiming Christ to a postmodern world - Loscalzo, Craig A. (Downers grove, IL IVP, 2000)
Includes bibliiographical references and index.
Keywords: Preaching; Apologetics; Postmodernism -- religious aspects -- Christianity